2011
DOI: 10.1080/15321819.2010.538109
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Specific Polyclonal Antibody With High Affinity to Atorvastatin and Its Employment in the Development of Elisa for Determination of Atorvastatin in Plasma

Abstract: For the first time, a polyclonal antibody with high affinity to atorvastatin (ATR) was generated. The high specificity of the antibody for ATR among its structural analogues and co-administered therapeutic agents was proved. The antibody was employed in the development of enzyme-linked immunosorbent assay for quantitation of ATR in plasma. The assay was validated over a working range of 0.2-5 ng/mL. The intra- and interassay precisions were satisfactory; the coefficients of variations were ≤5%. The accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The intervals for each immunization is 2 weeks. 44 Two weeks after the last immunization, the antiserum was collected. The sensitivity of antibodies was tested by slide agglutination method and the results showed that the polyclonal antibody could agglutinate with MO-1 at the minimum concentration of 1:640.…”
Section: B Preparation and Characterization Of Rabbit Anti-mo-1 Antimentioning
confidence: 99%
“…The intervals for each immunization is 2 weeks. 44 Two weeks after the last immunization, the antiserum was collected. The sensitivity of antibodies was tested by slide agglutination method and the results showed that the polyclonal antibody could agglutinate with MO-1 at the minimum concentration of 1:640.…”
Section: B Preparation and Characterization Of Rabbit Anti-mo-1 Antimentioning
confidence: 99%